Hyperhomocyst(e)inaemia, but not MTHFR C677T mutation, as a risk factor for non-arteritic ischaemic optic neuropathy. Issue 7 (1st July 2001) - Weger, Martin; Stanger, Olaf; Deutschmann, Hannes; Simon, Michael; Renner, Wilfried; Schmut, Otto; Semmelrock, Jürgen; Haas, Anton
Abstract : BACKGROUND/AIMS: Hyperhomocyst(e)inaemia has been identified as a strong risk factor for stroke, myocardial infarction, and deep vein thrombosis. A point mutation of methylene tetrahydrofolate reductase (MTHFR C677T) has been associated with increased plasma homocyst(e)ine levels. To investigate whether hyperhomocyst(e)inaemia and/or MTHFR C677T mutation are associated with non-arteritic ischaemic optic neuropathy (NAION), a case-control study including 59 consecutive patients with NAION and 59 controls matched for age and sex was performed. METHODS: Fasting plasma homocyst(e)ine levels, MTHFR C677T genotypes, and plasma levels of folate and vitamin B-12 were determined. RESULTS: Mean plasma homocyst(e)ine levels were significantly higher in patients than in controls (11.8 (SD 5.7) μmol/l v 9.8 (2.5) μmol/l, p = 0.02). The odds ratio for patients with homocyst(e)ine levels exceeding the 95th percentile of control homocyst(e)ine levels was 5.8 (95% CI 1.5–21.4). Mean plasma folate levels were significantly lower in patients than in controls (4.3 (1.7) ng/ml v 5.5 (1.9) ng/ml, p = 0.001), whereas plasma vitamin B-12 levels did not differ significantly. Prevalence of the MTHFR C677T mutation was not significantly increased in patients with NAION compared with controls. CONCLUSION: These results suggest that hyperhomocyst(e)inaemia, but not MTHFR C677T mutation is associated with NAION. Determination of plasma homocyst(e)ine levels might be of diagnostic value in patients with NAION.